Efektivitas Penggunaan Sistem SiAKU dalam Pengelolaan Pariwisata di Koperasi Desa Wisata Candirejo - Resta Azzahra Zuhrotun Nisa; Mulyo Budi Setiawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This exploration expects to decide and anlyzne the viability of involving the Siaku framework in the travel industry the executives at the Candirejo The travel industry Town Helpful. The examining strategy utilized was 15 respondents. To be specific agreeable workers who were ready to finish up this survey. This examination utilizes a different direct relapse investigation model utilizing the t test and f test on SPSS 22 programming. Prior to leading the examination, an external model test was done first with the Ordinariness Test, Linearity Test, f Test, and t Test. To decide the worth of every marker, utilizing the linkert scale level, which is as numbers 5, 4, 3, 2, 1. Estimation is done involving a poll as a Likert scale comprising of proclamations that should be replied by respondents by giving a score as per the degree of understanding or conflict. The consequences of this exploration show that at the same time, the viability of utilizing the Siaku framework, usage of the Siaku framework, and convenience of the Siaku framework essentially affect the interest of Siaku framework clients. Somewhat, the viability of utilizing the Siaku framework, utiliztion of the Siaku framework, and usability of the Siaku framework altogether affect the interest in clients of the Siaku framework for representatives of the Candirejo The travel industry Town Agreeable. Candirejo the travel industry town is a travel industry situated in Candirejo Town, Borobudur Locale, Magelang Rule, Focal Java Territory. This vacationer town serves an assortment of visit bundles with the goal that it gets many visits from individuals who need to travel, yet for recording visit bundles it actually utilizes manual strategies so there are hindrances regarding recording.